Cross-Species Genome-Wide Analysis Reveals Molecular and Functional Diversity of the Unconventional Interferon-ω Subtype - Shields, Lauren E.; Jennings, Jordan; Liu, Qinfang; Lee, Jinhwa; Ma, Wenjun; Blecha, Frank; Miller, Laura C.; Sang, Yongming (Frontiers in Immunology, 2019)
Innate immune interferons (IFNs), particularly type I IFNs, are primary mediators regulating animal antiviral, antitumor, and cell-proliferative activity. These antiviral cytokines have evolved remarkable molecular and functional diversity to confront ever-evolving viral threats and physiological regulation. We have annotated IFN gene families across 110 animal genomes, and showed that IFN genes, after originating in jawed fishes, had several significant evolutionary surges in vertebrate species of amphibians, bats and ungulates, particularly pigs and cattle. For example, pigs have the largest but still expanding type I IFN family consisting of nearly 60 IFN-coding genes that encode seven IFN subtypes including multigene subtypes of IFN-α, -δ and -ω. Whereas subtypes such as IFN-α and -β have been widely studied in many species, the unconventional subtypes such as IFN-ω have barely been investigated. We have cross-species defined the IFN evolution, and shown that unconventional IFN subtypes particularly the IFN-ω subtype have evolved several novel features including: 1) being a signature multi-gene subtype expanding primarily in mammals such as bats and ungulates, 2) emerging isoforms that have superior antiviral potency than typical IFN-α, 3) highly cross-species antiviral (but little anti-proliferative) activity exerted in cells of humans and other mammalian species, and 4) demonstrating potential novel molecular and functional properties. This study focused on IFN-ω to investigate the immunogenetic evolution and functional diversity of unconventional IFN subtypes, which may further IFN-based novel antiviral design pertinent to their cross-species high antiviral and novel activities.